Penegakan Hukum pada Kejahatan Cyber Crime Produsen yang Mempekerjakan Endorsement untuk Mempromosikan Kosmetika Ilegal Melalui Instagram - Edward Haryadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Internet users in Indonesia are increasing, in 2021 the development of Internet use is increasing rapidly as many as 7,000 samples come from Indonesia and all provinces in Indonesia and is growing from 8.9% to 73.7%, equivalent to 196.7 million internet users. Internet use is mostly used for social media such as Instagram. However, not all Instagram users can use Instagram wisely, so many cases of cyber crime still occur in Indonesia. So this research will discuss how law enforcement deals with cybercrime by manufacturers who employ endorsements to promote illegal cosmetics via Instagram. Using normative research methods activities that will examine internal aspects (to solve problems that exist within) positive law. For cases that occur, law enforcement can be applied such as imposing criminal sanctions as explained in the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions Article 9 in conjunction with Article 62 paragraph 1 of the Law Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection which reads Business actors who violate the provisions referred to in Article 8, Article 9, Article 9, Article 10, Article 13 paragraph (2), Article 15, Article 17 paragraph (1) letter a , letter b, letter c, letter e, paragraph (2), and article 18 shall be punished with imprisonment for a maximum of 5 (five) years or a fine of up to Rp. 2,000,000,000.00 (two billion rupiah). Suggestions that consumers are obliged to report if a case like this occurs so that the implementation in law enforcement will run smoother and be eradicated quickly, similar cases will no longer exist.